Linear Concurrent Constraint Programming: Operational and Phase Semantics - Fages, François; Ruet, Paul; Soliman, Sylvain (Information and computation, 2001)
In this paper we give a logical semantics for the class CC of concurrent constraint programming languages and for its extension LCC based on linear constraint systems. Besides the characterization in intuitionistic logic of the stores of CC computations, we show that both the stores and the successes of LCC computations can be characterized in intuitionistic linear logic. We illustrate the usefulness of these results by showing with examples how the phase semantics of linear logic can be used to give simple “semantical” proofs of safety properties of LCC programs.